Lignin bioconversion and upgrading to value-added products by marine protist, Thraustochytrium striatum - Li, Xiang (Kansas State University, 2019)
Lignin, an important component of lignocellulose, has been regarded as a promising feedstock for biofuel and bioproducts. For lignin utilization and upgrading, diverse strategies have been applied including thermochemical and biological ways. In this study, lignin-derived materials were used as carbon source and converted into bioproducts through microbial fermentation by a novel species, Thraustochytrium striatum. It was found that this strain was able to utilize various types of lignin compounds and produce fatty acids and carotenoids simultaneously. In the screening of several lignin model compounds as carbon sources, T. striatum can grow on most compounds at different concentrations, while achieving the best growth in 3,4-dihydroxybenzoic acid (3,4-DHBA) and 4-hydroxybenzoic acid (4-HBA). In both batch and fed-batch cultivation modes, T. striatum can accumulate a significant amount of long-chain fatty acids and carotenoids. T. striatum was also proven to degrade polymeric lignin. However, the depolymerization ability of T. striatum was relatively weak and therefore the fermentation process was optimized to improve lignin degradation and utilization. Among different nitrogen sources tested, the inorganic NH₄Cl was the best and application of organic nitrogen sources would inhibit the utilization of lignin. Mineral elements were able to improve lignin utilization by functioning as co-factors of ligninolytic enzymes and inducing their production at transcriptional level. Different external lignin depolymerization systems including commercial laccase, fungal secretome and Fenton reagent were observed to develop synergistic effects with T. striatum. In the presence of laccase both cell growth and lignin utilization were improved, while different kinds of laccase employed different mechanisms. The fungus-derived laccase was indicated to primarily work on breakdown of inter-unit linkages in lignin molecules, and plant-derived laccase possibly attacked aromatic ring structure. With the function of laccase, more low-molecular-weight fragments would be generated, and laccase-catalyzing reaction would shift the equilibrium toward depolymerization and prevent repolymerization of smaller fragments. On the contrary, lignin peroxidase-dominant fungal secretome and Fenton reagent facilitate lignin degradation while not cell growth. Black liquor prepared from corn stover alkaline pretreatment was also studied as a lignin-rich waste stream of bioprocessing and biorefinery. T. striatum was found to grow with black liquor and reached the cell mass concentration of 5.2 g/L under optimal conditions (pH=7, NH₄Cl=2 g/L) and reduce total lignin concentration of black liquor from 8.18 to 3.09 g/L within 7-day incubation. Aromatic monomers including p-coumaric acid, ferulic acid, vanillin, and syringaldehyde were observed to be consumed and converted while polymeric lignin fragments were also depolymerized and degraded. A strong adaptation of T. striatum to a wide pH range (3~9) was also observed during black liquor fermentation. The investigation on metabolism of T. striatum has identified diverse peroxidase and laccase-type enzymes for lignin depolymerization and multiple pathways for aromatic compounds degradation.
Keywords: Biofuel; Lignin bioconversion; Marine protist; Microbial metabolism